Stochastic Stability of Genetic Regulatory Networks with Mixed Delays - Wang, Zhengxia; Liu, Guodong; Huang, Darong; Song, Jun (International Journal of Sensors Wireless Communications and Control, 2013)
In this paper, the asymptotical stability of stochastic genetic regulatory networks with time-varying delays and continuous distributed delays are investigated. The constraint that derivative of time-varying delays must be smaller than 1 is relaxed, and the activation functions are of more general descriptions, which generalize and improve the earlier methods. Based on the Lyapunov-Krasovskii functional approach and linear matrix inequality (LMI) techniques defined on convex set, stability criteria for stochastic delayed genetic regulatory networks are established in the form of LMIs, which can be easily verified. Numerical example is also given to demonstrate the effectiveness of the proposed criteria.
Keywords: Distributed delays